Realistic Mathematics Education: Unlocking Problem-Solving Potential in Students - Miharja, Marenda Atika; Bulayi, Makungu; Triet, Le Viet Minh (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The purpose of this study was to explore the role of Realistic Mathematics Education (RME) in improving students' mathematical problem-solving skills and learning strategies in the classroom. This study also analyzed the effectiveness of the RME approach and students' and teachers' perceptions of the approach. Methodology: This study used a mixed method with a quasi-experimental design (pretest-posttest control group) and a case study. Data were collected using problem-solving tests, observation sheets, and interviews. The research instruments included context-based test questions, observation guides, and interview guides. Data analysis was carried out using statistical tests using SPSS and thematic analysis for qualitative data. Main Findings: The main results of this study indicate that the Realistic Mathematics Education (RME) approach significantly improved students' mathematical problem-solving skills compared to the conventional method. The mean posttest scores of students in the RME group were higher, with consistent improvement. Observations showed more active student engagement, use of visual aids, and contextual relevance in learning. Interviews revealed positive perceptions of teachers and students towards the effectiveness of the RME approach. Novelty/Originality of this study: This study is interesting since it thoroughly examines how well Indonesian students, particularly those in junior high school, can solve mathematical problems through Realistic Mathematics Education (RME). In addition to examining students' opinions and teachers' learning practices, this study offers a fresh perspective on the RME approach's growth within the local educational setting.